Records of Radio Aurora at Syowa Station, Antarctica from March 1966 to January 1968 - オセ; ハセガワ; タケウチ; ニシムタ; イソベ; OSE, M.; HASEGAWA, S.; TAKEUCHI, T.; NISHIMUTA, I.; ISOBE, T. (National Institute of Polar Research, 1969)
P(論文) departmental bulletin paper